If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 + -1X + 6x = 43 Solving -2 + -1X + 6x = 43 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '2' to each side of the equation. -2 + -1X + 2 + 6x = 43 + 2 Reorder the terms: -2 + 2 + -1X + 6x = 43 + 2 Combine like terms: -2 + 2 = 0 0 + -1X + 6x = 43 + 2 -1X + 6x = 43 + 2 Combine like terms: 43 + 2 = 45 -1X + 6x = 45 Add '-6x' to each side of the equation. -1X + 6x + -6x = 45 + -6x Combine like terms: 6x + -6x = 0 -1X + 0 = 45 + -6x -1X = 45 + -6x Divide each side by '-1'. X = -45 + 6x Simplifying X = -45 + 6x
| P-16=32 | | B/(1/3)=8/21 | | 5w^2-28=31w | | w^2+8w=60 | | 0.5c=10 | | B/(1/3) | | 36x^2+60s=-25 | | a/b=10a | | -4/11y=16/33 | | 3x^2-30x=-63 | | 7x-4x=-45 | | 48+d=60 | | 8+5ln(6x)=13 | | 36s^2+60s=60s | | 3x+4y-7x+2y= | | M-5=18 | | 8x+247+6x+185=180 | | 7x-4x=45 | | 52-n=24 | | 5r/r | | 4(3x-8)=39 | | 33+c=54 | | 0.09a=9 | | 28+b=50 | | 12m-2m=90 | | 31-x=16 | | 0.1m=5 | | m+33=20 | | A+12=25 | | 0.02f=48 | | -4(3p+2)-45=5(2p+7) | | 2x^2-13x-19=0 |